2004
DOI: 10.1194/jlr.m300309-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atorvastatin versus fenofibrate on apoB-100 and apoA-I kinetics in mixed hyperlipidemia

Abstract: Kinetics of apo B and apo AI were assessed in 8 patients with mixed hyperlipidemia at baseline and after 8 weeks of atorvastatin 80 mg q.d. and micronised fenofibrate 200 mg q.d. in a cross-over study. Both increased hepatic production and decreased catabolism of VLDL accounted for elevated cholesterol and triglyceride concentrations at baseline. Atorvastatin significantly decreased triglyceride, total, VLDL and LDL cholesterol and apo B concentrations ( ؊ 65%, ؊ 36%, ؊ 57%, ؊ 40% and ؊ 33%, respectively, P Ͻ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
56
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 57 publications
(64 reference statements)
16
56
3
Order By: Relevance
“…In our study, no significant effect of atorvastatin on apoA-I PR or FCR was observed. These results are in agreement with previously published studies indicating no effect of atorvastatin on the kinetics of apoA-I (6,(40)(41)(42)(43). The change in HDL-C with atorvastatin was independent of apoA-I kinetics.…”
Section: Discussionsupporting
confidence: 83%
“…In our study, no significant effect of atorvastatin on apoA-I PR or FCR was observed. These results are in agreement with previously published studies indicating no effect of atorvastatin on the kinetics of apoA-I (6,(40)(41)(42)(43). The change in HDL-C with atorvastatin was independent of apoA-I kinetics.…”
Section: Discussionsupporting
confidence: 83%
“…The latter observation was further supported by the significant reduction of RLP-C, a clinical parameter of remnants. The underlying metabolic mechanisms for these reductions are likely due to the increased catabolic rate, as consistently demonstrated by two recent kinetics studies (31,32). Although TG-rich lipoproteins are heterogeneous in size and composition, whereby in association with atherosclerosis, large VLDL, which possesses the highest capacity for inducing macrophage lipid loading, is preferentially reduced by fenofibrate (34).…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have focused on the effects of fenofibrate on li-indicate that increased HDL-C by fenofibrate is likely due to an increased production of apoA-I (31,32), together with decreased cholesteryl ester transfer protein activity (19) and increased ABCA1 (33). Overall, its observed alteration of HDL makes fenofibrate an ideal agent for strengthening the anti-atherogenic properties of HDL, when used in hypertriglyceridemic patients.…”
Section: Discussionmentioning
confidence: 99%
“…8). Clinical results demonstrated that atorvastatin did not change the production rate (PR) or fractional catabolic rate (FCR) of ApoA-I 113) . Administration of atorvastatin to mice did not significantly change ApoA-I expression in the liver and reduced ABCA1 and CETP expressions in the liver, indicating that the HDL-elevating effect of atorvastatin may be mediated mainly by CETP inhibition 59) .…”
Section: ) Rctmentioning
confidence: 99%